(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The article analyzes the state of the sanatorium-resort complex of the Republic of Uzbekistan and the dynamics of its development. The problems and specific features of the market for sanatorium and resort services are identified, and the structure of their regional market is characterized.